Management of Sigmoid Cancer In dr Cipto Mangunkusumo Hospital during 2008–2011 - Wahyu Sriningsih; Ibrahim Basir; Benny Philippi (Ikatan Ahli Bedah Indonesia, 2014)
A retrospective analysis was performed to sigmoid cancer cases in the digestive surgery division of Cipto Mangunkusumo Hospital during the period of 2008–2011. Fifty–two cases were analyzed for metastases, stages and histopathology; mortality and morbidity were calculated for anastomotic leakage, 3–year survival, and incidence of local recurrence. Three–year survival analysis was performed using Kaplan–Meier based on staging and histopathology. The overall operative mortality was 1.9%, and the anastomotic leakage incidence was 8.1%. The incidence of local recurrence was 9.1%. The 3–year survival rates based on Dukes Staging were as follows: 100% survival for Dukes A, 95.5% for Dukes B and 61.1% for Dukes C and 0% for Dukes C. The 3–year survival rates in sigmoid cancer according to histopathology were 73.5% for well differentiated, 63.6% for moderately differentiated and 100% for poorly differentiated (sample size was one patient, could not be assessed), with 50% survival for mucinous histopathology. The overall survival in this sigmoid cancer study was 69.2%.